The contribution to the scattering of electrons in the magnetoresistance of multilayers of nonmagnetic metals - Protsenko, I.Yu.; Odnodvorets, L.V.; Protsenko, S.I.; Shumakova, M.O. (Вопросы атомной науки и техники, 2016)
The semiphenomenological model that describes the scattering of electrons in the implementation of the phenomenon magnetoresistance (MR) three-layer film based on non-magnetic metals were proposed. The quantitative characteristic of the MR is so-called magnetic resistance coefficient βB = dlnR/dB, the value of which on the field dependence not only of the mean free path of the electrons, and a specular parameter and transmission parameters at the grain boundary and interfaces. Запропонована напівфеноменологічна модель, яка описує процеси розсіювання електронів при реалізації явища магнітоопору (МО) тришарової плівки на основі немагнітних металів. Кількісною характеристикою МО виступає так званий магнітний коефіцієнт опору βB = dlnR/dB, величина якого визначається польовою залежністю не тільки середньої довжини вільного пробігу електронів, а і коефіцієнтів дзеркальності зовнішніх поверхонь плівки, проходження межі зерен та інтерфейсів. Предложена полуфеноменологическая модель, которая описывает процессы рассеивания электронов при реализации явления магнитосопротивления (МС) трехслойной пленки на основе немагнитных металлов. Количественной характеристикой МС является так называемый магнитный коэффициент сопротивления βB = dlnR/dB, величина которого определяется полевой зависимостью не только средней длины свободного пробега электронов, а и коэффициентов зеркальности внешних поверхностей пленки, прохождения границы зерен и интерфейсов.